2016
DOI: 10.1111/febs.13911
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of steroid binding and oxidation by the cytochrome P450 CYP109E1 from Bacillus megaterium

Abstract: Cytochrome P450 monooxygenases (P450s) are attractive enzymes for the pharmaceutical industry, in particular, for applications in steroidal drug synthesis. Here, we report a comprehensive functional and structural characterization of CYP109E1, a novel steroid‐converting cytochrome P450 enzyme identified from the genome of Bacillus megaterium DSM319. In vitro and whole‐cell in vivo turnover experiments, combined with binding assays, revealed that CYP109E1 is able to hydroxylate testosterone at position 16β. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 82 publications
0
37
1
Order By: Relevance
“…Bioinformatic mining of the B. megaterium DSM319 genome previously led to identification of four genes putatively encoding for cytochrome P450 enzymes (CYP102A1, CYP106A1, CYP109E1, and CYP109A2) . Here, we focus on CYP109A2, the remaining P450 that has not been studied in detail yet.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bioinformatic mining of the B. megaterium DSM319 genome previously led to identification of four genes putatively encoding for cytochrome P450 enzymes (CYP102A1, CYP106A1, CYP109E1, and CYP109A2) . Here, we focus on CYP109A2, the remaining P450 that has not been studied in detail yet.…”
Section: Resultsmentioning
confidence: 99%
“…The substrate‐free CYP109A2 crystallized in an orthorhombic space group ( P 2 1 2 1 2 1 ), with four monomers in the asymmetric unit and a solvent content of 50%. The crystal structure was solved at 2.7 Å resolution by the molecular replacement method, using the previously determined structure of CYP109E1 (sequence similarity 45%, Protein Data Bank [PDB] entry http://www.rcsb.org/pdb/search/structidSearch.do?structureId=5L90, ) as a search model (see Table for data collection and refinement statistics). All four CYP109A2 molecules have well‐defined electron density, except for the 15 or 16 N‐terminal residues and the C‐terminal His 6 ‐tags, for which no electron density was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CYPs such as CYP106A1, CYP106A2, CYP109B1, CYP109E1, CYP154C3, CYP154C5, CYP260A1, and CYP260B1, originating from bacterial sources, are known to hydroxylate steroids . CYP154C8 shows high similarity with CYP154C3 (74 %) and CYP154C5 (66 %), both of which are reported to hydroxylate steroids at C16α.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequence identity of this novel C. apiculatus enzyme is 39% to CYP109B1, 44% to CYP109C1, 43% to CYP109C2 and 38% to CYP109D1. Studies on the steroid hydroxylating CYP109E1 from B. megaterium (36% identity to CYP109Q5) showed that this enzyme is more closely related to the steroid hydroxylase CYP106A1 in comparison with the already characterized CYP109 enzymes (Jóźwik et al ., ). Classification into a P450 family thus represents a strong evidence for a particular substrate spectrum; this is reflected by CYP109B1 and CYP109E1 that also functionalize a broad spectrum of substrates including steroids, fatty acids and terpenes (Girhard et al ., ; Putkaradze et al ., ).…”
Section: Discussionmentioning
confidence: 97%